The magic ring, Student's book level 2 - Moutsou, E; S.Parker, Mike , Carl (Paramount Enterprise, London, 2013)
PARA MMGR LEVEL-2: THE MAGIC RING ELEMENTARY STUDENT'S BOOK Author: OSCAR WILDE ISBN: 9789694945118 Publisher: MM PUBLICATIONS (E. MOUTSOU & CO O.E.) Category: SCHOOL TEXTBOOK | ENGLISH Series: MM GRADED READERS Level: Primary BookCover: Paperback Number Of Pages: 39 Volume Number 0 Number Of Volumes 0 Edition No: 1